Mind of her own the evolutionary psychology of women - Campbell Anne (Oxford OUP, 2002)
A fascinating and intellectually deep tour of the evolutionary psychology of woman. Campbell's book provides insights into some of the most profound mysteries of humane nature, why women form status hierarchies, why they battle for reputation, and the ce
Keywords: Evolutionary psychology; Women psychology